2007
DOI: 10.1080/87565640701190734
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Handedness and Footedness in Switched and Nonswitched Brazilian Left-Handers: Cultural Effects on the Development of Lateral Preferences

Abstract: In Western societies most left-handers who are pressured to write with the right hand resist the pressure. Searleman and Porac (2001, 2003) studied North American participants and proposed that mixed left-handers, more so than consistent left-handers, would be likely to successfully acquire right-handed writing skills on a long-term basis. In accordance with their two-phenotype hypothesis, the majority of switched left-handers (SLH) in their studies exhibited right-sided asymmetries on other handedness tasks s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
2
15
0
3
Order By: Relevance
“…The compulsory use of the non-preferred foot to perform actions that usually are not part of their actions leads the body to create new standards of action. This feature meets the views of various authors that highlight the multidimensional and dynamic characteristic of motor behaviour (Martin & Porac, 2007;Teixeira & Okazaki, 2007;Zverev, 2006). The presented results, in line with the studies of several authors (Andrade, 2012;Cobalchini & Silva, 2008;Haaland & Hoff, 2003;Teixeira, 2001;Teixeira et al, 2003), supports the conclusion that the functional asymmetry of the lower limbs tends to reduce when there is an increase of systematic training on the non-preferred limb.…”
Section: Discussionsupporting
confidence: 94%
“…The compulsory use of the non-preferred foot to perform actions that usually are not part of their actions leads the body to create new standards of action. This feature meets the views of various authors that highlight the multidimensional and dynamic characteristic of motor behaviour (Martin & Porac, 2007;Teixeira & Okazaki, 2007;Zverev, 2006). The presented results, in line with the studies of several authors (Andrade, 2012;Cobalchini & Silva, 2008;Haaland & Hoff, 2003;Teixeira, 2001;Teixeira et al, 2003), supports the conclusion that the functional asymmetry of the lower limbs tends to reduce when there is an increase of systematic training on the non-preferred limb.…”
Section: Discussionsupporting
confidence: 94%
“…Of the Right Shift respondents, 51% indicated that the pressures were applied in a punitive fashion (i.e., slapping, restraint of the hand) while only 28% of the Left Shift individuals reported such experiences, x 2 (1, N0119)06.86, pB.01. The finding of a significant difference in the method used to apply the rightward pressures between these two groups, with those applied to the Right Shift group being more frequently punitive when compared to the Left Shift group, is supportive of a distinction made by Wile (1932) and discussed by Martin and Porac (2007). Wile argued for the presence of resistant and not-so-resistant groups of left-handed children who are put into an environment where pressures are applied to convert to right-hand writing.…”
Section: Discussionsupporting
confidence: 51%
“…Edinburgh Handedness Inventory; Oldfield, 1971) or footedness (i.e. Waterloo Footedness Questionnaire-Revised; Elias, Bryden, & BulmanFleming, 1998;Martin & Porac, 2007) in elite players. We took a more direct approach, which included the assessment of ball contacts with the dominant and non-dominant hand for the execution of different skills during regular basketball competitions, as used previously by Carey et al (2001) to assess the foot preference of soccer players.…”
mentioning
confidence: 99%